Intravenous infusion of nicotinamide adenine dinucleotide (NAD+) versus nicotinamide riboside (NR): a retrospective tolerability pilot study in a real-world setting - Reyna, Kirsten; Heinzen, Greer; Patel, Nikita; Ritter, Marie; Siojo, Alexandra; Legere, Henry; Pojednic, Rachele (Frontiers in Aging, 2026)
BackgroundNicotinamide adenine dinucleotide (NAD+) is a cofactor for NAD+-dependent enzymes that regulate DNA repair, cellular metabolism, and immune function. Supplementation with NAD+ and its precursors is commonly used to prevent age-related disease and extend healthspan. Commercial clinical and wellness settings increasingly provide intravenous (IV) NAD+ and nicotinamide riboside (NR) despite limited evaluation of safety and effectiveness. These considerations are important, as NAD+ and its precursors differ in reported side effects, cellular uptake, and metabolism. This study sought to compare commercially administered NAD+ IV and NR IV in humans by evaluating infusion time, tolerability, safety markers, and metabolic outcomes.MethodsA retrospective review of electronic medical records was conducted in clients from a commercial setting. Participants received four consecutive days of 500 mg NAD+ IV or NR IV, with 30 days follow-up. Primary outcomes included reported symptoms, total infusion time, blood pressure, resting heart rate, and biomarker assessments (ALT, AST, hsCRP, BUN/creatinine, and TSH). Exploratory analyses included metabolic biomarkers (HbA1c, fasting glucose, HDL-C, LDL-C, and triglycerides).ResultsTolerability differed between groups. Participants that received NAD+ IV reported moderate to severe gastrointestinal symptoms, increased heart rate, and chest pressure during infusions. Participants receiving NR IV experienced minor tongue, jaw, and arm tingling and mild cramping during infusion. All symptoms resolved upon infusion completion. Moderate to severe symptoms with NAD+ IV resulted in longer infusion times compared to NR IV, averaging 97 min versus 37 min, respectively. No significant changes were observed in ALT, AST, hsCRP, BUN/creatinine, or TSH. Alkaline phosphatase (ALP) decreased significantly in the NAD+ IV group only, with values remaining within normal reference ranges. The NR IV group demonstrated a significant reduction in HbA1c, whereas the NAD+ IV group showed a significant reduction in HDL-C. Neither group exhibited changes in fasting glucose or LDL-C over the 30-day period.ConclusionThis study directly compared commercially administered NAD+ IV and NR IV, providing preliminary real-world evidence of infusion tolerability and short-term safety. Exploratory metabolic outcomes were variable and warrant further investigation. Additional studies are needed to evaluate dosage and effectiveness beyond 30 days.